Experimental Study on Dynamic Mechanical Characteristics and Energy Evolution of Sandstone under Cyclic Impact Loading - Xicai Gao; Huan Xia; Xinyu Wang; Cheng Zhao; Jianhui Yin (Shock and Vibration)
In order to study the dynamic mechanical properties of the surrounding rock of roadway in deep mines with rock burst, cyclic impact compression tests of sandstone under different impact velocities were carried out by using the split Hopkinson pressure bar (SHPB) test system, and the dynamic stress-strain curves of the samples under cyclic impact loads and the relationship between energy dissipation and impact numbers were analyzed. The results show that, as the impact loading times increase, the initial elastic modulus of sandstone samples decreases, the peak stress decreases, and the peak strain increases; the average strain rate increases. The cumulative damage of sandstone samples under impact load is significantly affected by impact velocity and times. During the cyclic impact test, the reflected energy of sandstone increases with the increase of impact numbers, while the transmitted energy decreases and the absorbed energy increases; the cumulative specific energy absorption variable is introduced, and the cumulative specific energy absorption value of the samples increases with the increase of impact numbers, which can better characterize the variation of energy accumulation and dissipation of sandstone samples under cyclic impact.